A new species of the genus Oxyporus Fabricius (Coleoptera: Staphylinidae: Oxyporinae) in Yunnan, China - Li, Guo-Feng; Wang, Chun-Mei; Li, Hong-Wei; Hou, Yun-Ping (Zootaxa, 2015)
Oxyporus (Oxyporus) kunmingius sp. nov. is described from Yunnan, China. Color images of the habitus and aedeagus of the new species are included. A key to the genus Oxyporus of Yunnan species is provided.